Access to Justice for People with Autism Spectrum Disorder: Comparative Analysis and Areas of Opportunity for its Consolidation of this Community in Peru - Noronha Val, Diego Alonso (2024)
Autism Spectrum Disorder (ASD) involves the combination of various cognitive conditions that make interaction and communication diffi[1]cult for the person who presents it. That is, we are faced with an intellectual deficiency that qualifies as a disability, in accordance with the international instruments that regulate the matter. This situation makes its members vulnerable to ineffective state actions in different areas of development. The impossibility of obtaining a quick and timely diagnosis, through the competent institutions, not only aggravates their psychological condition, but also prevents them from being granted legal treatment according to their needs. Thus, even though, around 2014, in Peru, Law n.o 30150 was enacted, formally dedicated to the protection of people with this disorder and from which the National Plan for People with Autism Spectrum Disorder 2019-2021 was formulated , none of these instruments address access to justice as a relevant aspect to consider for the consolidation of this community in the country. The legislative reality is different in other countries in the region, such as Chile, Bolivia and Mexico, which, following the parameters of the Brasilia Rules, propose normative provisions conventionally appropriate for the treatment of these people in the judicial sphere. Thus, this research aims to identify the main material barriers that in Peru prevent people with ASD from properly accessing justice, and then carry out a comparative analysis from which the areas of opportunity and improvement will be obtained, allowing to structure a lege ferenda approach to the matter.